Statistics of glinting clouds observed by DSCOVR and geostationary satellites - Várnai, Tamás; Marshak, Alexander; Kostinski, Alexander (Frontiers in Remote Sensing, 2026)
This study examines how frequently the specular reflection of sunlight—that is, sun glint—reveals the presence of ice crystals that maintain a steady horizontal orientation. The study analyzes data from the Earth Polychromatic Imaging Camera (EPIC) onboard the Deep Space Climate Observatory (DSCOVR) spacecraft and from collocated images taken by geostationary satellites. The analysis of spatio-temporal variations in glint frequency over vegetated land surfaces reveals that (a) year-to-year variations are modest with no clear trends; (b) glints typically occur 7%–8% more frequently than previously estimated; (c) glints are most frequently observed during the May-August period, and over Asia. The results also show that glint frequency drops for very high (>12–13 km) clouds but otherwise displays little sensitivity to geostationary satellite-provided cloud parameters, namely altitude, optical thickness, and particle size. This is because glints come from horizontal crystals near cloud tops whereas geostationary satellites characterize the entire cloudy column. This suggests that glint-free passive satellite observations are not well-suited for estimating the likelihood of horizontal ice crystals and underlines the importance of analyzing direct sun glint observations from satellite instruments such as EPIC.